2005
DOI: 10.1094/mpmi-18-0397
|View full text |Cite
|
Sign up to set email alerts
|

RAR1, ROR1, and the Actin Cytoskeleton Contribute to Basal Resistance to Magnaporthe grisea in Barley

Abstract: The fungus Magnaporthe grisea, the causal agent of rice blast disease, is a major pathogen of rice and is capable of producing epidemics on other cultivated cereals, including barley (Hordeum vulgare). We explored the requirements for basal resistance of barley against a compatible M. grisea isolate using both genetic and chemical approaches. Mutants of the RAR1 gene required for the function of major resistance gene-mediated resistance and mutants of the ROR1 and ROR2 genes required for full expression of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 33 publications
8
52
0
1
Order By: Relevance
“…Barley ROR2 is the functional homolog of Arabidopsis PEN1 and is required for mlo-mediated broad-spectrum resistance against all tested host barley powdery mildew isolates (Collins et al 2003;Freialdenhoven et al 1996). However, ROR2 is not essential for resistance against strains of the rice blast fungus Magnaporthe grisea that can infect barley (Jarosch et al 2005). The penetration mechanism and hemibiotrophic lifestyle of M. grisea is very similar to that of Colletotrichum species, i.e., both parasites develop melanized appressoria that penetrate directly to produce intracellular hyphae inside living plant cells before later switching to necrotrophy (Koga et al 2004;Perfect et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Barley ROR2 is the functional homolog of Arabidopsis PEN1 and is required for mlo-mediated broad-spectrum resistance against all tested host barley powdery mildew isolates (Collins et al 2003;Freialdenhoven et al 1996). However, ROR2 is not essential for resistance against strains of the rice blast fungus Magnaporthe grisea that can infect barley (Jarosch et al 2005). The penetration mechanism and hemibiotrophic lifestyle of M. grisea is very similar to that of Colletotrichum species, i.e., both parasites develop melanized appressoria that penetrate directly to produce intracellular hyphae inside living plant cells before later switching to necrotrophy (Koga et al 2004;Perfect et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Mechanistically this nonhost type of resistance appears to be based on a more efficient execution of different defense strategies, i.e., formation of papillae and onset of the hypersensitive response, also known from attacked epidermal cells in the host interaction. 7,8 Here, we summarize our efforts to characterize the NHR of barley against Magnaporthe at the molecular level using transcriptome profiling and VIGS.…”
mentioning
confidence: 99%
“…Evaluation of the immune response to M. oryzae in the osrar1 rice mutant Recent evidence suggests that resistance to virulent pathogens in Arabidopsis and barley is dependent on the level of the RAR1 protein (Holt et al, 2005;Jarosch et al, 2005). We previously showed that OsRAR1 functionally rescues the disease resistance of the atrar1 mutant to the virulent P. syringae pv.…”
Section: Resultsmentioning
confidence: 99%
“…tomato (Pst) DC3000 (Holt et al, 2005) and of barley to the virulent M. oryzae isolate (Jarosch et al, 2005). In rice, the overexpression of OsRAR1 increases the resistance to the virulent Xanthomonas oryzae pv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation